2020
DOI: 10.1093/ptep/ptaa025
|View full text |Cite
|
Sign up to set email alerts
|

Charged spherically symmetric Taub–NUT black hole solutions in $f(R)$ gravity

Abstract: f (R) theory is a modification of Einstein general relativity which has many interesting results in cosmology and astrophysics. To derive solutions for black holes solution in this theory is difficult due to the fact that it is fourth order differential equations. In this study, we use the quadratic form of f (R) = R + βR 2 − 2Λ, where β is a dimensional parameter and Λ is the cosmological constant, to find the solutions of new 4-dimension spherically symmetric non-charged and charged NUT and Taub-NUT black ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…The behaviors of the quasi-local energies are shown in Figure 1(d) which also shows that E(r 2 ) is also positive and an increasing function of r 2 . Finally, we use Equations ( 46), (47), and (48) in Equation ( 45) to calculate the Gibbs free energies and obtain…”
Section: The Thermodynamics Of the Black Solution (37)mentioning
confidence: 99%
See 2 more Smart Citations
“…The behaviors of the quasi-local energies are shown in Figure 1(d) which also shows that E(r 2 ) is also positive and an increasing function of r 2 . Finally, we use Equations ( 46), (47), and (48) in Equation ( 45) to calculate the Gibbs free energies and obtain…”
Section: The Thermodynamics Of the Black Solution (37)mentioning
confidence: 99%
“…The Figure tells that the quasi-local energy is positive and an increasing function of r 2 . Finally, using Equations ( 46), (47), and (48) in Equation ( 45), we find the Gibbs free energies. The behaviors of these free energies are shown in Figure 2(d), which tells us the free energy is positive and an increasing function of r 2 , again.…”
Section: Thermodynamics Of Multi-horizon Black Hole (37) With Negativ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main feature of f (R) gravity is that an arbitrary Ricci scalar describes the Lagrangian density. The model that is based on f (R) gravity is one of the most elementary theories among several modified theories of gravity used to explain it [15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, to generalize these theories, another important parameter that should be studied is the impact of electric charge.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of f (R) gravity (for a review see [22,23]) several black hole solutions have been found recently. Vacuum solutions were discussed in [24][25][26][27][28], while charged black hole solutions were also found in [29][30][31][32][33][34][35][36]. In [37], dynamical black holes, characterized by time-varying apparent horizons, in various theories of gravity, including the f (R) theory were investigated.…”
Section: Introductionmentioning
confidence: 99%